UPAYA MENINGKATKAN HASIL BELAJAR IPA MELALUI PENERAPAN MODEL MIND MAPPING - Heti Purnamadewi (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2020)
This research was motivated by the low science learning outcomes in class VII MTs Negeri 2 Pangandaran. The research objective was to improve the science learning outcomes of class VII-V students of MTs Negeri 2 Pangandaran through a mind mapping learning model. The method used is classroom action research. The research was conducted in 2 cycles, each cycle consisting of two meetings. The research subjects were students of class VII-C MTs Negeri 2 Pangandaran, totaling 30 students, consisting of 14 male students and 16 female students. The results showed that the average student learning outcomes increased from 54.55 before the pre-action to 63.33 in the first cycle of meeting 1 and increased to 70 in the first cycle of meeting 2. In cycle 2 the average learning outcomes increased from 78 in findings. 1 to 84 at the meeting 2. Based on the completeness data it can be concluded that the application of the mind mapping model can improve the learning outcomes of class VII-C students in the science subject at MTs Negeri 2 Pangandaran.